The role of livestock and poverty in the rural area of Puno - Paredes Mamani, Rene Paz (2018)
The objective of the study was to contrast the existence of poverty traps in the rural area of the department of Puno, as well as to measure the impact of the stock of the asset earned on the reduction of poverty in the period 2004-2015. The results in the first place using the pseudo-panel methodology show that there are type II poverty traps at the level of the region, the rural area and the livestock sector of Puno. Secondly, the incidence of stock of livestock assets on the reduction of poverty in the period 2004-2015 was not evident. Third, the results suggest that monetary poverty, chronic poverty and recent poverty depend significantly on the number of members of the household, the number of recipients of income in the household, the Aymara and Quechua mother tongue, the possession of electricity, level of education of heads of household, lack of housing for sanitary services, the number of hectares of land and the number of parcels. The effect of these factors is greater on chronic poverty with respect to recent poverty